Recent advancements of flow cytometry: new applications in hematology and oncology. (January 2014) - Woo, Janghee; Baumann, Alexandra; Arguello, Vivian
<x xml:space="preserve">Abstract</x> Flow cytometry offers great diagnostic opportunities in the vast majority of hematologic and oncologic diseases with multiple cellular and molecular information within an individual cell. We will discuss various applications of flow cytometry, particularly in hematology and oncology, in addition to general principles and limitations of flow cytometry. They include nucleic acid analyses in cancer cells, new methods for assessing rare circulating tumor cells and disease-specific applications in malignancy with emphasis on diagnosis and treatment of hematologic malignancy, including minimal residual disease. With improvement of monoclonal antibodies, fluorescence and laser technology, flow cytometry now offers new avenues of assessing cellular functionality through examination of intracellular compartments. High-throughput quantitative analysis, advancements of in vivo flow cytometry and assessment of minimal residual diseases, as exampled in patient stratification and prediction of leukemia therapeutic response, will further make flow cytometry indispensable in medicine.